2011
DOI: 10.1128/mcb.05737-11
|View full text |Cite
|
Sign up to set email alerts
|

BID Binds to Replication Protein A and Stimulates ATR Function following Replicative Stress

Abstract: Proapoptotic BH3-interacting death domain agonist (BID) regulates apoptosis and the DNA damage response. Following replicative stress, BID associates with proteins of the DNA damage sensor complex, including replication protein A (RPA), ataxia telangiectasia and Rad3 related (ATR), and ATR-interacting protein (ATRIP), and facilitates an efficient DNA damage response. We have found that BID stimulates the association of RPA with components of the DNA damage sensor complex through interaction with the basic clef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…26 The apoptotic function of Bid is predominantly mediated by its caspasecleavage sites 21,22 and BH3 domain, 38 while Bid executes its function in the DNA damage signaling pathways by its Atm/Atr phosphorylation sites 26,37 its unique Helix 4 and RPA-interacting domains. 19,39 Bid À / À mice spontaneously develop chronic myelomonocytic leukemia (CMML) and the tumor cells display chromosomal aberrations. 20 It is likely that both the apoptotic and DNA damage function of Bid work synergistically to maintain hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…26 The apoptotic function of Bid is predominantly mediated by its caspasecleavage sites 21,22 and BH3 domain, 38 while Bid executes its function in the DNA damage signaling pathways by its Atm/Atr phosphorylation sites 26,37 its unique Helix 4 and RPA-interacting domains. 19,39 Bid À / À mice spontaneously develop chronic myelomonocytic leukemia (CMML) and the tumor cells display chromosomal aberrations. 20 It is likely that both the apoptotic and DNA damage function of Bid work synergistically to maintain hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In addition, we have demonstrated a role for Bid in the DDR to replicative stress mediated by Atr. 19,21,33 To probe Atmindependent roles for Bid in vivo, we have crossed Bid À / À mice to Atm À / À mice. Surprisingly, we found that loss of Bid increases the latency of leukemogenesis in Atm À / À mice.…”
Section: Discussionmentioning
confidence: 99%
“…Bid thus functions at the level of the DNA damage sensor complex, and integrates DNA replicative stress signals. [19][20][21] A recent report, using mice harboring Bid mutated in the Atm/Atr phosphorylation sites that has been knocked into the Bid locus, has demonstrated that Atmmediated Bid phosphorylation has a role in protecting HSCs from irradiation and oxidative stress, suggesting the possibility that Bid may have a more general role in sensing stress. 22 An elegant series of experiments has recently demonstrated in the mouse model of lymphomagenesis induced by g irradiation that tumorigenesis is driven by repeated cycles of hematopoietic progenitor cell death, inducing compensatory mobilization of HSC and progenitor cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…BCL-2 family members have been reported to affect DNA damage repair (8)(9)(10), and MCL-1 depletion can decrease Chk1 phosphorylation and increase phosphorylated H2AX (␥-H2AX) in etoposide-treated cells (11). Moreover, MCL-1 has also been shown to interact with several DNA damage response (DDR) proteins, including ␥-H2AX, NBS1, and Ku70 (10,12,13), but the molecular details as to how MCL-1 may regulate DNA double-strand break (DSB) repair have not been established.…”
mentioning
confidence: 99%